Barriers and Perceptions Among Engineering Students in Conducting Online Learning During COVID-19 Outbreaks - Ibrahim, Akhmad Fadli; Yodang, Yodang; Ihsan, Nur (IJECA (International Journal of Education and Curriculum Application), 2021)
Since the last of 2019, the Corona Virus Disease (COVID-19) identified and its spreading globally as pandemic disease. During the COVID-19 outbreaks all countries all over the world change in terms of regulation include educational system. The majority of countries were implementing online learning from elementary to higher education level. However, how students’ barriers and perceived during attending the online learning were still unidentifed. This study aims to investigate the engineering students’ barriers and perception in online learning environment during the pandemic. This study applied cross-sectional study were participants recruited from engineering schools both mining and civil engineerings. There are 170 students participated in this study, and predominantly who age range 17-20 (81.2%), men (84.1%), mining engineering (55.9%), freshmen (47.6%),  students’ barriers in severe level (50%), and students’ perception in good perception level (55.9%). The statistic analysis using Chi-square test found that there is no effect of socio-demographics on students’ barriers and perception in online learning. While, the correlation test shows that barriers and perceptions has positive correlation in online learning.